2020
DOI: 10.6061/clinics/2020/e1750
|View full text |Cite
|
Sign up to set email alerts
|

Impact of microablative fractional radiofrequency on the vaginal health, microbiota, and cellularity of postmenopausal women

Abstract: We aimed to evaluate the effectiveness of microablative fractional radiofrequency (MAFRF) in the non-hormonal treatment of genitourinary syndrome of menopause. METHODS: We examined the cases of 55 postmenopausal women before and after treatment with regard to their vaginal health index (VHI), vaginal microbiota, vaginal pH, and cell maturation. Three applications of MAFRF were performed in the vagina/vaginal introitus. During the treatment, six vaginal smears were obtained and stained with the Papanicolaou sta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 18 publications
(19 citation statements)
references
References 19 publications
0
18
0
Order By: Relevance
“…However, a hormonal treatment is not the only option; a recent study by Sarmento et al showed a statistically significant increase in the percentage of Lactobacillus spp. and a progressive decrease in vaginal pH when microablative fractional radiofrequency was used for the treatment of genitourinary syndrome of menopause [ 93 ]. Finally, vaginal microbiome transplantation from healthy donors to women suffering from intractable and recurrent bacterial vaginosis can be used to reconstitute vaginal flora towards a Lactobacillus -dominated vaginal microbiome [ 94 , 95 ], with potential consequences for UTI incidence.…”
Section: Applying Novel Insights To Clinical Practice: Can We Redumentioning
confidence: 99%
“…However, a hormonal treatment is not the only option; a recent study by Sarmento et al showed a statistically significant increase in the percentage of Lactobacillus spp. and a progressive decrease in vaginal pH when microablative fractional radiofrequency was used for the treatment of genitourinary syndrome of menopause [ 93 ]. Finally, vaginal microbiome transplantation from healthy donors to women suffering from intractable and recurrent bacterial vaginosis can be used to reconstitute vaginal flora towards a Lactobacillus -dominated vaginal microbiome [ 94 , 95 ], with potential consequences for UTI incidence.…”
Section: Applying Novel Insights To Clinical Practice: Can We Redumentioning
confidence: 99%
“…Therefore, with an equal 1:1:1 allocation rate, according to the results of a pilot study, where data came from 55 volunteers, 28 accepting an alpha of 0.05 and a beta risk…”
Section: Sample Sizementioning
confidence: 99%
“…The first pilot study on vaginal and vestibular MFR for genitourinary menopausal syndrome reported that the intervention was effective on atrophy symptoms, was well tolerated, and was associated with a rapid recovery; however, the study included only a few women (21). More robust studies have confirmed that MFR can be beneficial in the treatment of patients with genitourinary disorders (22,23). Sarmento et al (22) conducted a randomized trial on the effects of MFR on vaginal health, microbiota, and cellularity in postmenopausal women.…”
Section: ' Discussionmentioning
confidence: 99%
“…More robust studies have confirmed that MFR can be beneficial in the treatment of patients with genitourinary disorders (22,23). Sarmento et al (22) conducted a randomized trial on the effects of MFR on vaginal health, microbiota, and cellularity in postmenopausal women. The preliminary results indicated that MFR considerably improved the vaginal microenvironment, similar to that expected in women with adequate estrogen concentrations.…”
Section: ' Discussionmentioning
confidence: 99%
See 1 more Smart Citation